Industry 4.0 and Supply Chain Performance in the Oil and Gas Industry (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this study is to investigate industry 4.0 and supply chain performance. Extant literature was reviewed. Secondary data such as E-books, journal articles projects were used. Exploratory research design was used for the study. Based on the review literature, it was revealed that, integrated supply chain performance measurement system (SCPMS) is paramount for an efficient supply chain management (SCM) at inter-organizational and beyond-the-boundary processes. The recent technological innovations (internet of things (IoTs), big data, and web-based communication systems) revamp the SCPMS through effective data collection, information sharing, and framework integration among the different SC partners across nations. The study recommend for further research on the obstacles facing industry 4.0 and supply chain performance in the oil and gas industries across nations.